2007
DOI: 10.1016/j.tpb.2006.11.001
|View full text |Cite
|
Sign up to set email alerts
|

How patch configuration affects the impact of disturbances on metapopulation persistence

Abstract: Disturbances affect metapopulations directly through reductions in population size and indirectly through habitat modification. We consider how metapopulation persistence is affected by different disturbance regimes and the way in which disturbances spread, when metapopulations are compact or elongated, using a stochastic spatially explicit model which includes metapopulation and habitat dynamics. We discover that the risk of population extinction is larger for spatially aggregated disturbances than for spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 40 publications
3
47
0
Order By: Relevance
“…In an 512 ecological context Vuilleumier et al (2007) and in an epidemiological context 513 Rhodes & Anderson (1996) concluded that increasing the movement distance 514 maximises the probability of persistence. They considered patches as the unit 515 of study and had many unoccupied patches in the population.…”
Section: Results 349mentioning
confidence: 99%
“…In an 512 ecological context Vuilleumier et al (2007) and in an epidemiological context 513 Rhodes & Anderson (1996) concluded that increasing the movement distance 514 maximises the probability of persistence. They considered patches as the unit 515 of study and had many unoccupied patches in the population.…”
Section: Results 349mentioning
confidence: 99%
“…Another limitation of the formula is that it assumes there is no spatial correlation in the network dynamics of patch destruction and recreation (Johst & Drechsler 2003;Vuilleumier et al 2007). We found that our formula approximates the simulated MMLT with acceptable precision if the correlation length is less than about 25 per cent of the network radius.…”
Section: Discussionmentioning
confidence: 94%
“…Pools closer to the sea have a lower desiccation risk due to the inflow of sea water, but more predators may be present as well. Such correlations of environmental variables are common, and many metapopulation or metacommunity models have been used to address the effect of spatial or temporal autocorrelations of environmental factors (Vuilleumier et al 2007, Elkin & Possingham 2008, Büchi et al 2009). Recent experimental work is showing that the intrinsic links of environmental factors (e.g.…”
Section: Discussionmentioning
confidence: 99%